Manajemen Waktu dan Self Regulated Learning pada Siswa - Lu'luatul Usroh; Nadhirotul Laily; Fatchul Munir (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
This study aims to examine the effect of time management with self-regulated learning on high school students. The sample in this study amounted to 133 students. The measuring instrument in this study uses a self-regulated learning scale developed by Boekaerts (2000) with a reliability coefficient of 0.929. The time management scale is based on three-time management factors developed by Macan (1994) with a reliability coefficient of 0.884. The data analysis technique used is simple linear regression analysis. The results obtained in this study have a significant positive effect between time management and self-regulated learning in Class XI SMA students. The implication of this research is that time management ability has an influence on students' self-regulated learning, so that the higher the time management, the higher the students' self-regulated learning ability.